THE EFFECT OF USING THE CANVA PLAY EDU APPLICATION AS A DIGITAL ASSESSMENT TOOL ON ELEMENTARY SCHOOL SCIENCE LEARNING OUTCOMES - Ika Dian Rahmawati; Rika Wulandari; Husniatun Na’miyah; Reskiya Ramadani (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2026)
The integration of digital technology in education has transformed learning and assessment practices; however, assessment in elementary schools remains largely conventional and less engaging, limiting students’ participation and higher-order thinking skills. Although prior studies have examined digital learning media, limited research has specifically explored gamification-based digital assessment tools in improving elementary science learning outcomes. This study aims to analyze the effect of using Canva Play Edu as a digital assessment tool on students’ learning outcomes. This study employed a quasi-experimental design with a nonequivalent control group involving 38 fourth-grade students at SDN Kemayoran 02 Bangkalan. Data were collected through pretest and posttest and analyzed using the Shapiro–Wilk test, Mann–Whitney U test, and N-gain analysis. The results showed that the experimental group outperformed the control group, with mean scores of 86.63 and 81.68, respectively (p < 0.05). The N-gain score of 0.80 (high category) and N-gain percentage of 80.41% (very effective) indicate a substantial improvement in learning outcomes. These findings suggest that Canva Play Edu is an effective gamification-based digital assessment tool that enhances both learning outcomes and student engagement in elementary science education.